The Analysis of the System for the Selection of Leaders in Uzbekistan in Ancient and Middle Ages (Global Journal of Science Frontier Research, 2021)
Public administration is a type of social governance that governs society Some theorists believe that public administration in the broadest sense is the regulatory activity of the state the influence of particular subjects on social relations However public administration is also the activity of the executive branch of government to provide guidance in certain areas and objects of public life Training and appointment of potential young people for public administration has always been a topical issue for all countries In ancient times from the 4th century BC to the 8th century AD the emergence of the Arab caliphate from the formation of the first state the practical formation of the election of leaders and officials in the system of government and administration is determined by the presence of older or middle-aged people in leadership positions The Middle Ages IX-XVIII centuries were a period of development growth and emergence of scientific theories and doctrines in the field of public administration and the selection of leaders and officials mainly in the appointment of young people to senior positions based on dynasties